Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

ajprincess

  • 3 years ago

plzz help. How do I prove p∧(pvq)=p using laws of algebra of propositions

  • This Question is Closed
  1. JamesJ
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Do you have this theorem? Let A(x) be a statement involving x. If ~x ^ A(x) is always false, then A(x) = x. If so, then notice ~p ^ p ^ (pvq) = FALSE, hence p ^ (pvq) = p. Another way is ....

  2. JamesJ
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    p∧(pvq) = (p^p) v (p^q) = p v (p ^ q), because p^p = p = p , because if p is false then both p and p^q are false.

  3. timo86m
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    pvq would have to be = 1

  4. timo86m
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    1/vq=p

  5. timo86m
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    1/vq=p ^ that is not a :P

  6. ajprincess
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thanxxx a lott.

  7. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy